Peran Material Lokal Bambu dan Batu Padas Dalam Sistem Konstruksi Villa Ramah Lingkungan - Nasution, Aulia Muflih; Suwondoh, Rudi; Nasution, Mufti Ali (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The global construction sector contributes significantly to greenhouse gas emissions, accounting for approximately 32–34% of total global emissions. In Indonesia, the construction industry has been growing at an annual rate of 6.4–7.5%, increasing the demand for sustainable building materials. This study aims to evaluate the structural feasibility and sustainability of bamboo (Dendrocalamus asper) and sandstone as building materials through a synthesis of published laboratory data and conceptual design analysis. The results indicate that bamboo exhibits high mechanical strength that meets and exceeds minimum structural standards, while sandstone demonstrates adequate compressive strength and superior thermal insulation performance compared to conventional concrete. The integrated application of both materials in a 52 m² conceptual villa design resulted in a 49.4% reduction in embodied carbon and an 8.2% reduction in construction costs. The use of hybrid bamboo–steel connections further enhances seismic resistance and structural integrity. These findings confirm that bamboo and sandstone are viable, sustainable, and efficient local material alternatives for residential construction in tropical regions.